Validation of the Work Limitations Questionnaire in Brazilian Army military personnel - Umann, Juliane; Marques da Silva, Rodrigo; Akiko Kimura, Cristilene; Cauê Lopes, Vitor; Bellezi Guilhem, Dirce (Investigación y Educación en Enfermería, 2018)
Objective To validate the Work Limitations Questionnaire (WLQ) to measure presenteeism in Brazilian military personnel. Methods This is a test validation study conducted with 125 individuals of a military staff attending a Brazilian Army Unit. We applied a form with demographic and occupational variables and the WLQ, composed of 25 items. The construct validity was assed trough confirmatory factorial analysis. Results We confirmed the interdependent structure of the WLQ´s domains for explaining the presenteeism of the sample in four domains: outcome demand, mental demand, physical demand and time management. Most of items showed factorial loads between 0.5 and 0.7 and the adjustment (absolute and incremental) and residues indexes demonstrated satisfactory values. The Alphas in domains ranged from 0.68 (output demand) to 0.79 (time management) in domains, evidencing reliability for the WLQ. Conclusion We confirm the construct validity of the WLQ to assess presenteeism in Brazilian military staff. How to cite this article: Umann J, Silva RM, Kimura CA, Lopes VC, Guilhem DB. Validation of the Work Limitations Questionnaire in Brazilian Army military personnel. Invest. Educ. Enferm. 2018; 36(3):e06.